Development of artificial seed and preservation in Mimosa pudica L., an important medicinal plant in Bangladesh (Journal of Bio-Science, 2016)
Context: Mimosa pudica L. is an important medicinal plant belonging to the family- Mimosaceae has becoming a rare species in Bangladesh. The application of artificial seed technology using encapsulated shoot tips and nodal segments may contribute to the protection of rare and threatened medicinal plant like Mimosa pudica L.Objective: Synthetic seed technology has been developed for Mimosa pudica L. in order to develop an alternative protocol on propagation and conservation.Materials and Methods: For this purpose shoot tip and nodal segments obtained from in vitro grown plants were encapsulated with sodium alginate solution followed by subsequent immersion in CaCl2 solution. Different concentrations and combinations of growth regulators were used and explants were treated in alginate bead to investigate the hormonal effect on artificial seed germination. These encapsulated seeds were cultured either on MS medium with hormone (same growth regulators containing alginate beads) or MS0 (without hormone).Results: Highest shoot regeneration frequency (100%) were recorded when alginate beads were infused by MS medium supplemented with 2.0 mg/l BAP + 0.2 mg/l NAA and cultured in MS medium containing same growth regulators. When synthetic seed containing 2.0 mg/l BAP+0.2 mg/l NAA and cultured on MS0 medium, 54% explants produced multifarious root with shoot in both cases. Under different storage period encapsulated seed retained germination capacity even after preserving for 60 days at 4°C.Conclusion: For artificial seed production a suitable protocol established under this study for Mimosa pudica L. that provides an alternative method for micropropagation and its conservation. For long term storage of Mimosa pudica in Bangladesh this protocol would provide promising avenues for the easy transference of propagules and its improvement.J. bio-sci. 22: 89-99, 2014